Chemical kinetic interactions and sensitivity analyses for 2-ethylhexyl nitrate-doped PRF91 using a reduced mechanism. (1st December 2022) - Cho, Seokwon; Lopez-Pintor, Dario; Goldsborough, Scott
Highlights: The effects of doping PRF91 with 2-ethylhexylnitrate (EHN) were investigated. EHN enhances the reactivity of the fuel, but the effect is non-linear. EHN effect is lowest during the low-temperature regime and highest during NTC. EHN-doped fuel is more sensitive to intermediate-temp. chemistry than straight fuel. EHN-doped fuel is sensitive to NO2-to-NO reactions, especially at high temperature. Abstract: A numerical and experimental investigation about the chemical kinetic interactions between 2-ethylhexylnitrate (EHN) and PRF91 was performed in this study. Rapid compression machine experiments were conducted to investigate the effect of EHN on the autoignition reactivity of the fuel, and a reduced chemical kinetic mechanism was developed including an EHN sub-model. Experiments showed that the ignition delay decreases as the fuel is doped with EHN, but the effect of the doping level of EHN on the ignition is highly non-linear. Moreover, experiments showed that the EHN effectiveness is lowest during the transition between the low-temperature regime and the negative temperature coefficient (NTC) regime, and it rapidly increases as the temperature increases. Both detailed and (developed) reduced mechanisms were validated against the experimental results, allowing a more in-depth EHN-fuel chemistry study. Additionally, ignition delay sensitivity and EHN effectiveness sensitivity analyses were performed with the reduced mechanism to identify the reactions that control the interaction between EHN and the fuel. As the result, EHN thermal decomposition is only relevant for very low temperatures. The chemistry of EHN-doped fuel is more sensitive to intermediate temperature reactions than that of straight fuel, especially at lower temperatures, due to the effect of EHN on the NTC behavior of the fuel. Finally, the chemistry of EHN-doped fuel is very sensitive to NO2 -to-NO reactions, especially at high temperatures, because these reactions transform the NO2 generated by EHN into NO, which is a very effective fuel reactivity enhancer.